Exploring the “Can Do” and “Will Do” factors of human capital to enhance university performance - F. Fairuzzabadi; Mohamad Shaharudin Samsurijan; Syarifah Rahmawati; Zahri Hamat; Rustam Effendi (Research and Development in Education (RaDEn), 2024)
This study explores the "Can Do" and "Will Do" elements of human capital that impact university performance. Human capital, comprising both "Can Do" and "Will Do" elements, plays a pivotal role in driving organizational success, particularly in academic institutions. To investigate these elements within the university context, we conducted an exploratory qualitative research design using semi-structured face-to-face interviews with 12 purposely selected university practitioners and experts. The study results show that a high knowledge level, skills, capabilities, and experiences characterize the "Can Do" mindset. In contrast, the "Will Do" attitude encompasses personal traits, achievement motivation, and engagement with the job and institution. In conclusion, this research underscores the importance of cultivating a synergistic relationship between human capital's "Can Do" and "Will Do" aspects for driving sustainable improvements in university performance. By leveraging these insights, academic institutions can optimize their resources and empower their faculty to achieve greater success and impact.